CD39+ regulatory T cells attenuate allergic airway inflammation. Issue 6 (June 2015) - Li, P.; Gao, Y.; Cao, J.; Wang, W.; Chen, Y.; Zhang, G.; Robson, S. C.; Wu, Y.; Yang, J.
Summary Background The suppressive mechanism of regulatory T cells (Tregs) has remained incompletely clarified. Recent studies found that CD39 expressed by Tregs may participate in the immunoregulatory role of Tregs. CD39‐induced ATP hydrolysis and/or adenosine generation contribute to the suppressive mechanism of Tregs. Previous studies suggested that ATP is involved in allergic airway inflammation by acting on type 2 purinergic (P2) receptors, but the role of CD39 and CD39+Tregs in allergic airway inflammation has not been elaborated. Objective To investigate the role and underlying mechanism of CD39 expression by Tregs in allergic airway inflammation. Methods A model of allergic asthma was developed with ovalbumin–alum in female Cd39 wild type (Cd39+/+) and deficient (Cd39−/−) C57BL/6 mice. Foxp3‐GFP knock‐in Cd39+/+ and Cd39−/− mice were used to sort CD4+GFP+cells (Tregs) for exploring the role of CD39 expression by Tregs in allergic asthma. The effects of modulating CD39 activity with ARL67156 (inhibitor) or apyrase were also observed. Results ARL67156 greatly worsened airway inflammation including increased lung inflammatory cells infiltration, goblet cell hyperplasia, and higher levels of Th2 and Th17 cytokines in bronchoalveolar lavage fluid (BALF), accompanied by an increment in transcription factor (GATA‐3 and RORγt) and P2R (P2Y2, P2Y4 and P2Y6) mRNA expression in lungs. This potentiating effect was rescued by intratracheal injection of apyrase. Airway inflammation was markedly increased in Cd39−/− mice compared to Cd39+/+ mice. In contrast to CD39−Tregs, CD39+Tregs showed stronger suppressive effects on airway inflammation. In vitro suppression assay suggested that CD39+Tregs have more potent suppressive effect on cytokines secretion from CD4+CD25− responder T cells and the inhibitory effects were reduced by addition of adenosine A2A receptor antagonist. Conclusion CD39 expressed on Tregs participates in the regulation of limiting allergic airway inflammation by regulating extracellular ATP and/or adenosine. CD39 may represent a new therapeutic target for asthma.